Tanggung Jawab Perdata Notaris atas Kelalaian dalam Pembuatan Akta Autentik - Agustina, Lia (CV. Kurnia Grup, 2025)
This research analyzes the forms of notary's civil liability for negligence in making authentic deeds and the forms of legal protection provided to notaries. The background of this research is the increasing number of cases of authority abuse by notaries resulting in losses to the parties and third parties, as well as the imbalance between the idealism of the notary position as an independent public official and the reality of practice in society. The research problems formulated are: (1) what are the forms of notary's civil liability in making authentic deeds; and (2) what are the forms of legal protection for notaries. The method used is normative juridical with a statutory approach examining the Indonesian Civil Code and the Notary Office Law, as well as a case approach analyzing the West Java High Court Decision Number 09/PDT/2017/PT.BDG and the Supreme Court Decision Number 3121 K/Pdt/2018. The results show that notary's civil liability stems from their attributive authority and is based on unlawful acts (Article 1365 of the Indonesian Civil Code), which may include joint and several liability for material and immaterial compensation, deed cancellation, payment of dwangsom, and degradation of authentic deed's evidentiary power to that of a private deed (Article 1869 of the Indonesian Civil Code). This liability is personal and ongoing, not expiring even when the notary's position ends. As a counterbalance, notaries receive legal protection through the right to refuse testimony, internal professional forums (Supervisory Assembly and Notary Honor Council), the right to refuse making deeds, treatment as expert witnesses in court, and cultural protection in the form of a legal culture that respects the independence of the notary position. The Indonesian legal system has created a balance between accountability and professional protection for notaries.